1969
DOI: 10.1136/ard.28.5.471
|View full text |Cite
|
Sign up to set email alerts
|

The natural history of acute rheumatism.

Abstract: This paper presents an analysis of 1,033 cases of acute rheumatism and chorea followed until death or for 5 to 40 years after the onset. 56 of the patients died within 5 years of the onset, but of the remaining 977 the average follow-up was nearly 12 years; 451 were traced for more than 10 and 108 for more than 20 years. The majority of the first attacks (644/ 1033) occurred between the ages of 6 and 10. In 163 cases the age at onset was 5 or under and in 215 it was 11 to 15 years. These features are in accord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1976
1976
1988
1988

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Caution should, nevertheless, be exercised in making comparisons, since certain manifestations of rheumatic fever exhibit a marked tendency to vary with time. For example, both the frequency and severity of carditis and the frequency of chorea have declined substantially in developed countries over the last few decades (7,21). The reported incidence of chorea in some studies of rheumatic fever in India is lower than that found here and in Delhi (8), but is similar to the level recorded in developed countries in the past.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Caution should, nevertheless, be exercised in making comparisons, since certain manifestations of rheumatic fever exhibit a marked tendency to vary with time. For example, both the frequency and severity of carditis and the frequency of chorea have declined substantially in developed countries over the last few decades (7,21). The reported incidence of chorea in some studies of rheumatic fever in India is lower than that found here and in Delhi (8), but is similar to the level recorded in developed countries in the past.…”
Section: Discussionmentioning
confidence: 99%
“…This variation probably arose because no distinction was made between the clinical features of the initial attack and those of recurrences. With each successive recurrence, the heart disease becomes more extensive (6,7). Furthermore, in developing countries, the long journey to the hospital is usually undertaken when the patient develops disabling symptoms, such as congestive heart failure in the case of rheumatic fever; arthritis and arthralgia by themselves often receive indigenous treatment.…”
mentioning
confidence: 99%
“…of patients with rheumatic carditis re-developed it in subsequent attacks with more severe valve damage. Anti-streptococcal antibiotics given prophylactically greatly reduce the frequency of recurrent attacks of rheumatic fever (Perry, 1969).…”
Section: Discussionmentioning
confidence: 99%